2012
DOI: 10.1182/blood-2011-12-309153
|View full text |Cite
|
Sign up to set email alerts
|

How I treat immune thrombocytopenia: the choice between splenectomy or a medical therapy as a second-line treatment

Abstract: The paradigm for managing primary immune thrombocytopenia (ITP) in adults has changed with the advent of rituximab and thrombopoietin receptor agonists (TPO-RAs) as options for second-line therapy. Splenectomy continues to provide the highest cure rate (60%-70% at 5؉ years). Nonetheless, splenectomy is invasive, irreversible, associated with postoperative complications, and its outcome is currently unpredictable, leading some physicians and patients toward postponement and use of alternative approaches. An imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
162
0
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(175 citation statements)
references
References 81 publications
1
162
0
12
Order By: Relevance
“…Furthermore, many patients experience unsustained responses regardless of treatment choice. Current guidelines for ITP are clearer for frontline treatment, but very uncertain for second line and beyond [75]. Thus, too great a proportion of patients have a significant unmet medical need because they cannot easily and safely manage their disease.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, many patients experience unsustained responses regardless of treatment choice. Current guidelines for ITP are clearer for frontline treatment, but very uncertain for second line and beyond [75]. Thus, too great a proportion of patients have a significant unmet medical need because they cannot easily and safely manage their disease.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, both patients and physicians are increasingly reluctant to proceed to splenec-haematologica | 2013; 98(6) Relapse-free survival tomy as second-line therapy, and there is still lively international debate on the therapeutic algorithm of patients failing first-line corticosteroid treatment. 6,8,21 In this study, we report the largest cohort of ITP patients that was observed for such a long period of time (minimum 10 years) after splenectomy, with a particular focus on stable responders. Unlike previously published experiences, in the present paper, response to treatments was rated and classified according to current guidelines and terminology; 1 this might explain some possible differences in patients' outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, after rituximab administration, only 20-30% of patients maintain the response at five years, 12 with no conclusive data concerning the best timing of its use. 9,21,22 TPO-ra treatment is also effective but needs continuous administration. Moreover, no definitive safety data are available in the use of these agents over 5-6 years.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19] In view of these robust data, both drugs have been approved for adult chronic ITP in more than 80 countries and some groups consider them second-line treatment for chronic ITP. 5,20 However, in Europe, they are only authorized for use after splenectomy failure or when splenectomy is contraindicated.…”
Section: Introductionmentioning
confidence: 99%